Effectiveness of Digital Lactation Education on Breastfeeding Self-Efficacy among Postpartum Mothers - Ita Herawati; Jamilah Jamilah; Andhika Hartanty; Ani Lismawati; Mariani Mariani; Eva Cylvia Nurromadhoniyati; Sri Yuniasih (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Breastfeeding self-efficacy is a key factor influencing breastfeeding success among postpartum mothers. Low maternal confidence in breastfeeding remains a major barrier to achieving exclusive breastfeeding. The rapid development of digital technology provides opportunities to deliver lactation education through more accessible, interactive, and flexible media. This study aims to analyze the effectiveness of digital lactation education delivered through e-booklets, educational applications, telecounseling platforms, educational videos, and animated videos in improving breastfeeding self-efficacy among postpartum mothers. A quantitative approach with a quasi-experimental pretest-posttest design without a control group was employed. The sample consisted of 30–35 postpartum mothers selected through purposive sampling from several healthcare facilities. Breastfeeding self-efficacy was measured using the Breastfeeding Self-Efficacy Scale (BSES). Data were analyzed using parametric and nonparametric statistical tests according to data characteristics. The findings showed a significant increase in breastfeeding self-efficacy scores after the implementation of digital lactation education across all media types, with p-values < 0.05. These results indicate that digital lactation education is effective in enhancing postpartum mothers’ confidence in breastfeeding. The use of digital educational media can be recommended as an innovative strategy in midwifery services to support the success of exclusive breastfeeding programs.